Event-Specific Risk Factors Predicting Episodes of Unprotected Anal Intercourse with Male Nonregular Partners among Men Who Have Sex with Men Using Case-Crossover Study Design. (20th July 2014) - Li, Jinghua; Lau, Joseph T. F.; Gu, Jing; Hao, Chun; Lai, Coco H. Y.
Abstract : This study investigated event-specific factors that determine episodes of unprotected and protected anal intercourse (UAI and PAI) among 215 men who have sex with men (MSM), who used condoms inconsistently with nonregular partners (NRP) in the last six months, in Hong Kong. A case-crossover study design was used. Lower likelihood of episodes involving UAI with NRP was associated with (1) five partner attributes (NRP were <35 years old, at least three previous anal sex experiences with the NRP, perception that participant and the NRP had asymmetrical sexual experience, perception that the NRP was feminine, and liking toward the NRP; OR = 0.16–0.52), (2) six situational variables (the participant having had UAI with another man in the last week, having discussed condom use, perception that the NRP liked to use condom, partner's suggestion to have PAI, participant's suggestion to have PAI, and participant's plan to use condoms; OR = 0.11–0.39), and (3) four environmental/setting variables (condoms already placed at the venue, display of condom use promotion materials, participant's possession of a condom, and the NRP possessed a condom; OR = 0.27–0.45). HIV prevention targeting MSM should focus on event-specific protective factors, which may be different from those obtained from studies distinguishing condom users versus nonusers.